2019
DOI: 10.1021/jacs.9b04387
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Protonation Dramatically Affects the Membrane Permeability of Drug-like Molecules

Abstract: Permeability (P m) across biological membranes is of fundamental importance and a key factor in drug absorption, distribution and development. Although the majority of drugs will be charged at some point during oral delivery, our understanding of membrane permeation by charged species is limited. The canonical model assumes that only neutral molecules partition into and passively permeate across membranes, but there is mounting evidence that these processes are also facile for certain charged species. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 151 publications
7
86
0
1
Order By: Relevance
“…The focus on the neutral state of two drugs is also in agreement with recent studies by Clancy and co-workers where the neutral states of two hERG blockers (dofetilide and moxifloxacin) were found to be more stable than the charged ones in the narrow intra-cavity space in the study employing exhaustive Umbrella-Sampling simulations (Yang et al, 2020). It is important to stress that computational and experimental studies showed that various charged-states of the blockers exist in a highly dynamical equilibrium, where preference for a specific charge state of the drug can be shifted by the environment (membrane, binding pocket, or aqueous phase) (Shagufta et al, 2009;Carvalho et al, 2013;Demarco et al, 2018;Perissinotti et al, 2019;Yue et al, 2019).…”
Section: Structure Preparationsmentioning
confidence: 98%
“…The focus on the neutral state of two drugs is also in agreement with recent studies by Clancy and co-workers where the neutral states of two hERG blockers (dofetilide and moxifloxacin) were found to be more stable than the charged ones in the narrow intra-cavity space in the study employing exhaustive Umbrella-Sampling simulations (Yang et al, 2020). It is important to stress that computational and experimental studies showed that various charged-states of the blockers exist in a highly dynamical equilibrium, where preference for a specific charge state of the drug can be shifted by the environment (membrane, binding pocket, or aqueous phase) (Shagufta et al, 2009;Carvalho et al, 2013;Demarco et al, 2018;Perissinotti et al, 2019;Yue et al, 2019).…”
Section: Structure Preparationsmentioning
confidence: 98%
“…This approach, which integrates atomistic simulations and high-resolution experiments using human iPSCs, provides a vivid picture of cellular drug delivery and target engagement of molecules directed at membrane proteins. The significance of this approach is illustrated by its potential to distinguish and explain selective vs off-target effects early in the drug discovery process as well as its broad applicability to a variety of organ-and patient-specific human cell lines 41,42 and complementary experimental and computational tools 43-45 . The result is a powerful platform to accelerate the discovery and design of bioactive molecules with well-defined potency, selectivity, and cell permeability that can be applied for the systematic interrogation and pharmacological modulation of membrane protein function.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Therefore, understanding lipid-ligand interactions is paramount not only for designing the above-mentioned lipid therapies 3 or to assess the toxicity of compounds, but also to describe phenomena such as membrane permeability, which plays a key role in drug design and development. [17][18][19][20][21] The interaction and/or diffusion of a drug through a membrane is dependent on a variety of factors, among them, its ability to establish noncovalent interactions. In this scope, the formation of intra-or intermolecular hydrogen bonds (HBs) is a well known crucial factor affecting membrane-ligand interactions and permeability, hence determining pharmacological activity.…”
Section: Introductionmentioning
confidence: 99%